Pembuatan Recycle Screen Printed Carbon Electrode dan Aplikasinya untuk Deteksi Asam Galat dengan Teknik Voltammetri - Wulan Tri Wahyuni; Rany Zalvianita; Rudi Heryanto (Jurnal Kimia Sains dan Aplikasi, 2019)
Gallic acid is phenolic compound found in tea and act as antiradical agent. This compound is electrochemically active and could be detected using voltammetric technique. This study aims to obtain recycle screen printed carbon electrode (rSPCE) and applied it for voltammetric detection of gallic acid. rSPCE was prepared by modification of used SPCE working electrode using a mixture of graphite:polystyrene at ratio of 95:5, 90:10, and 85:15 (w/w). Graphite:polystyrene was suspended in chloroform and deposited on SPCE by drop casting method. Phosphate buffer 0.1 M at pH of 2.5, 3.5, and 7 were used as electrolyte solution in voltammetric detection of gallic acid. The optimum condition of gallic acid detection was obtained when phosphate buffer 0,1 M at pH of 2.5 and rSPCE in composition of graphite:polystyrene (95:5) used as electrolyte and working electrode, respectively. Gallic acid has 2 oxidation peaks at potential of 0.26 V and 0.63 V vs Ag/AgCl, respectively. At concentration of 1 – 5 mM, gallic acid and oxidation currents provide linear regression with the coefficient determination of 0.9947 and 0.9864, consecutively for peak number 1 and 2. Measurement of gallic acid at rSPCE 95:5 shows good precision with %RSD < 5%. rSPCE was successfully applied for voltammetric detection of gallic acid in standard solution with accuracy > 96%, however further development is needed before its application for gallic acid measurement in real sample such as tea extract.